(untitled) (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2022)
BAZNAS has an important role in social life in terms of welfare, but in reality there are still many problems from various aspects ranging from management that actually optimizes collection, there are two ways that BAZNAS Bangka Regency does, directly and indirectly. This study uses a qualitative-descriptive approach. The results show that the management of BAZNAS in Bangka Regency is in accordance with the practice carried out by optimizing collection by changing public awareness, conducting education to create a sense of caring for one another, giving rewards to people who are diligent in tithing, adding partners so that BAZNAS operations run well, and strengthening legal standing so that the scope of collection is carried out comprehensively so that it can help people in need. BAZNAS focuses on consumptive distribution because the main objective of BAZNAS is to assist the government in tackling poverty.